Durability of POFA-modified dense-graded cold mix asphalt - Usman, Kabiru Rogo; Mohd Rosli, Hainin; Satar, M.K.I.M.; Muhammad Naqiuddin, Mohd Warid; Bilema, Munder Abdullah Mohamed; Aliyu, Usman; A. J., Zulfiqar (IOP Publishing Ltd, 2022)
Cold mix asphalt (CMA) is a versatile and energy efficient mixture often prepared at ambient temperature. Efforts to improve the performance of CMA mixtures recorded appreciable success. Nonetheless, the critical performance measures of moisture and abrasive resistance still baffles researchers. Additionally, CMA’s design, production, testing, and site application is bedevilled by slow rate of strength gain, high void content, and absence of a globally acceptable mix design. This study aimed at assessing CMA’s durability measures using the modified Lottman (moisture damage) and Cantabro tests by adding a 3% palm oil fuel ash (POFA) as filler replacement and 3% cement. Fast-curing mixtures fabricated with a cationic quick-set (CQS-1h) and a rapid-set (RS-1K) emulsion both of medium viscosities with a nominal maximum aggregate size (NMAS) of 4.75 mm were evaluated. In addition to improving the Marshall volumetric properties, POFA’s inclusion is aimed at improving adhesion thereby enhancing the durability of the fine dense-graded cold mix asphalt (FGCMA-4.75 mm). The modified Marshall as stated in the asphalt institute (AI) manual series (MS-19) for dense-graded CMA was used for design. Results indicated that POFA reduces the void, improves stability, and enhance durability. Moreover, the CQS-1h has better durability for both control (FGCMA-C) and POFA-modified mixtures (FGCMA-P). While RS-1K has higher tensile strength in both dry and moisture-conditioned states with a higher tensile strength ratio (TSR) for both FGCMA-C and FGCMA-P mixtures. POFA’s pozzolanic capability proves effective in improving the durability and moisture damage resistance of FGCMA-P.